First cases of West Nile fever in Saratov region - Krasovskaya T.Yu. (Саратовский научно-медицинский журнал, 2013)
The aimofthe article is to provide assessment of the role of West Nile virus in the infectious pathology on the territory of the Saratov region. Material and methods. Clinical samples (blood, serum, cerebrospinal fluid, urine) taken from 27 patients with symptoms resembling West Nile fever, receiving treatment in infectious departments of hospitals in Saratov and the Saratov region were analyzed. Results. In 2012 forthe first time in the Saratov region 11 cases ofWest Nile fever were detected. Conclusion. Analysis of the current epidemiological situation on West Nile fever demonstrates the necessity of strengthening of prophylactic and counter-epidemic measures to prevent cases of this disease in the region.